ANALISIS MODEL PROPAGASI KOMUNIKASI BERGERAK PADA SISTEM GSM DI PT. XL AXITA PADANG - Fakhruddin Ahmad Nasution; Delsina Faiza; Khairi Budayawan (Universitas Negeri Padang, 2016)
This research based by the weak received signal received by the Mobile Station (MS) caused loss propagation trajecktory which allows the impending failure of calls and data connections. The purpose of this research is todiscover the impairment power received by MS. Monitored from the value of Rx Level and knowing the propagation model of Padang city urban areas in general.The method of measurement used is a Test Drive using TEMS Investigations software version 8.0. then analyzed with empirical models and models Okumura Hata, the results of the analysis compared with the standard value of Rx Level. This research was conducted in the morning and evening for five days.The analysis showed: (1) The signal quality measurements on base stations Terandam in average -81.6 dBm, and Hata model calculations on average -79.66 dBm, Okumura models average of -78.47 dBm, then the signal quality in good condition, BTS Simpang Haru is an average measurement of -82.7 dBm, and Hata model calculations on average -86.49 dBm, Okumura models average of -81.43 dBm, then the signal quality in good condition and the BTS Cendana Andalas in average measurement -80.03 dBm, and Hata model calculations on average -90.05 dBm, Okumura models average of -86.19 dBm, then the signal quality in a state of being. (2) Empirically propagation model for urban areas is a desert city in BTS Terandam Hata models, while BTS Simpang Haru and Sandalwood Andalas is a model Okumura. (3) Creep waves are blocked and then undergo reflection resulting trajectory taken further and further away, the received signal varies causing fluctuations in the signal and trigger fading, and failure in call and data. Keywords: MS, Rx Level, Drive Test, TEMS Investigation, transmitter, receiver and diffraction